Separate Filing (Splitsing) In Criminal Case Management - Hidayat Abdulah (Jurnal Daulat Hukum, 2018)
In the implementation of the criminal case handling a lot of things that can be done to perfect evidence is the failure by one of them is doing a separate filing (splitsing). In Article 142 Criminal Procedure Code stipulates that the public prosecutor has the authority to separate docket (splitsing) against each defendant if found lacking evidence and testimony, as well as other matters that are not included in the provisions of Article 141 of the Criminal Procedure Code. Separation of the case must be based on solely the purpose of examination. That's what makes the public prosecutor has the authority to determine the case file should be separated (splitsing) or not. The purpose for doing the separation of the case file (splitsing) is to facilitate the enforcement of the prosecutor when the court process, to strengthen the evidence for lack of evidence when the process of verification, then a criminal offense committed by the offender more than one and the same time one of these actors into the search list (DPO) which allow splitsing.Keywords: Separate Filing; The Criminal Case.